2012
DOI: 10.1136/medhum-2012-010203
|View full text |Cite
|
Sign up to set email alerts
|

Performance and palliative care: a drama module for medical students

Abstract: This paper describes an innovative 2 weeks module for medical students facilitated by drama educators and a palliative medicine doctor. The module incorporates drama, end-of-life care, teamwork and reflective practice. The module contents, practical aspects of drama teaching and learning outcomes are discussed. Various themes emerged from a study of Harold Pinter's play, The Caretaker, which were relevant to clinical practice: silence, power, communication, uncertainty and unanswered questions. Drama teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Our selection strategy yielded 49 articles . Of these, 35 presented empirical data and 14 were conceptual in nature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our selection strategy yielded 49 articles . Of these, 35 presented empirical data and 14 were conceptual in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Instructor transparency and participation in the process are both critical for creating trust, because students intuitively recognise that their engagement with the arts is a process of self‐disclosure that can easily be abused . Specific strategies that authors used to create a safe learning environment included developing a set of ground rules for the course and creating contract agreements . These strategies were seen as not only setting a particular context, but also a way of capitilising on the arts’ ability to bring people together and to create a community of learners.
‘We are a community of learners mining a work of art for its potential meaning… In retrospect, this sense of “we‐ness”, of the relationships in the foreground and the background, operated like metaphoric connective tissue that cushioned, supported, and structured the experiences.’
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Other novel interventions that may help overcome barriers include video conferencing, team-based learning, the use of simulation, online case-based modules, reading literature, and self-reflection. [29][30][31][32] The lack of experienced faculty also can be addressed. The End-of-Life Nursing Education Consortium (ELNEC) courses have been successfully used to prepare graduate nursing faculty to provide palliative care.…”
Section: Discussionmentioning
confidence: 98%
“…This theme perhaps saw the arts occupy their traditional role in medical education, whereby the arts are used as instruments to help develop such qualities as reflection, communication skills, critical thinking, leadership, access to tacit knowledge, empathy, appreciation of complexity and communities of practice in a variety of different groups that included undergraduate medical students, general practice trainees, teaching faculty staff, and mental health workers and their clients. Other studies suggested that using the visual arts in teaching can improve medical students’ observational and diagnostic skills …”
Section: Resultsmentioning
confidence: 99%